A continent-wide analysis of the shade requirements of red and western grey kangaroos. Issue 2 (2nd April 2016) - Roberts, J. A.; Coulson, G.; Munn, A. J.; Kearney, M. R.
ABSTRACT: Foraging time may be constrained by a suite of phenomena including weather, which can restrict a species' activity and energy intake. This is recognized as pivotal for many species whose distributions are known to correlate with climate, including kangaroos, although such impacts are rarely quantified. We explore how differences in shade seeking, a thermoregulatory behavior, of 2 closely-related kangaroo species, Macropus rufus (red kangaroos) and M. fuliginosus (western grey kangaroos), might reflect differences in their distributions across Australia. We observed foraging and shade-seeking behavior in the field and, together with local weather observations, calculated threshold radiant temperatures (based on solar and infrared radiant heat loads) over which the kangaroos retreated to shade. We apply these calculated tolerance thresholds to hourly microclimatic estimates derived from daily-gridded weather data to predict activity constraints across the Australian continent over a 10-year period. M. fuliginosus spent more time than M. rufus in the shade (7.6 ± 0.7 h versus 6.4 ± 0.9 h) and more time foraging (11.8 ± 0.5 h vs. 10.0 ± 0.6 h), although total time resting was equivalent (∼8.2 h). M. rufus tolerated 19°C higher radiant temperatures than M. fuliginosus (89°C versus 70°C radiant temperature). Across Australia, we predicted M. fuliginosus to be more restricted to shade than M. rufus, with higher absolute shade requirements farther north. These results corroborate previous findings that M. rufus is more adept at dealing with heat than M. fuliginosus and indicate that M. rufus is less dependent on shade on a continental scale.